2000
DOI: 10.1089/neu.2000.17.1179
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Improves Long-Term Neurologic Outcome Versus Fentanyl After Traumatic Brain Injury in Rats

Abstract: Despite routine use of fentanyl in patients after traumatic brain injury (TBI), it is unclear if it is the optimal sedative/analgesic agent. Isoflurane is commonly used in experimental TBI. We hypothesized that isoflurane would be neuroprotective versus fentanyl after TBI. Rats underwent controlled cortical impact (CCI) and received 4 h of N2O/O2 (2:1) and either fentanyl (10 microg/kg i.v. bolus, 50 microg/kg/h infusion) or isoflurane (1% by inhalation) with controlled ventilation. Shams underwent identical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 50 publications
1
69
0
Order By: Relevance
“…A 2 min anesthetic washout period was used to reduce the potential confounding effects of general anesthesia (17). At the end of the anesthetic washout, burst suppression was seen on EEG, at which point the ventilator was turned off (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2 min anesthetic washout period was used to reduce the potential confounding effects of general anesthesia (17). At the end of the anesthetic washout, burst suppression was seen on EEG, at which point the ventilator was turned off (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At 2 min prior to asphyxia isofluorane/N 2 O was discontinued. This anesthetic washout was performed to reduce the confounding effects of inhaled anesthetics (17). Previous pilot experiments testing the anesthetic regimen in uninjured PND 16 -18 rats monitored with scalp electrodes showed that EEG activity began to recover in frequency and amplitude by 2 min, just as animals were emerging from general anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…To ensure that anesthetic differences between groups did not produce differential neuroprotective effects (Statler et al, 2000(Statler et al, , 2006, the mice in the sham and CCI-only groups were exposed to an identical duration of anesthesia as those in the HS and CCI + HS groups. We carried out studies until each group had 10 mice for the entire 21-day outcome protocol.…”
Section: Monitoring Protocolmentioning
confidence: 99%
“…We hypothesized that the differential results may be attributed to the choice of anesthetic agents, based upon previous studies identifying isoflurane as a neuroprotectant [50,51,52]. To test this hypothesis, neuropathological markers of injury were compared in the brains of Avertin- versus isoflurane-anesthetized mice at 24 h after an equivalent impact severity.…”
Section: Resultsmentioning
confidence: 99%